2023
DOI: 10.3389/fpsyt.2023.1165153
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers in psychiatric autoimmune encephalitis: a retrospective cohort study

Abstract: BackgroundPsychiatric autoimmune encephalitis (pAE) is a growing field of interest in diagnosis and therapy in psychiatric hospitals and institutions. This study investigates the relevant extent to which there are potential biomarkers in cerebrospinal fluid (CSF) that can differentiate against a cohort with neurodegenerative disease.MethodsWe included in this study a total of 27 patients with possible and definite psychiatric autoimmune encephalitis and compared with a cohort with CSF-based AD (n = 27) differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, although the large Daguano Gastaldi cohort study (Daguano Gastaldi et al, 2022) also demonstrated that the presence of autoantibodies in psychotic disorders (with similar prevalence in healthy subjects) is not disease-defining, it is also clear that at least their overall prevalence of 17% in psychotic disorders certainly affects a considerable proportion of patients, which clearly limits the need to clarify at least theoretically conceivable pathogenicity. The second most frequent syndrome in definitive psychiatric autoimmune encephalitis was a parahallucinatory syndrome (after the most frequent psychoorganic syndrome (Hansen et al, 2023) -a finding consistent with autoimmune psychosis as one of the major subtypes of autoimmune encephalitis.…”
Section: Discussionmentioning
confidence: 80%
“…However, although the large Daguano Gastaldi cohort study (Daguano Gastaldi et al, 2022) also demonstrated that the presence of autoantibodies in psychotic disorders (with similar prevalence in healthy subjects) is not disease-defining, it is also clear that at least their overall prevalence of 17% in psychotic disorders certainly affects a considerable proportion of patients, which clearly limits the need to clarify at least theoretically conceivable pathogenicity. The second most frequent syndrome in definitive psychiatric autoimmune encephalitis was a parahallucinatory syndrome (after the most frequent psychoorganic syndrome (Hansen et al, 2023) -a finding consistent with autoimmune psychosis as one of the major subtypes of autoimmune encephalitis.…”
Section: Discussionmentioning
confidence: 80%